Effect of Supplementation of Aloe Vera Juice on the Carcass Traits of Japanese Quails - P, Jogeswar; P, Ponnuvel; D, Sreekumar; P K, Mandal; R, Ganesan; N, Elanchezhian (Journal of Meat Science, 2023)
An experiment was carried out using 300 Namakkal strain of Japanese  quails from day old to five weeks of age to study the effect of aloe vera  juice supplementation at different concentrations through drinking water  on growth performance. The birds were divided into four treatment  groups with three replicates in each treatment and each replicate had  25 birds. The four treatment groups consisted of control group without  supplementation of aloe vera juice (T0), treatment group 1 (T1) with  supplementation of aloe vera juice at the rate of 1 per cent, treatment  group 2 (T2) with 1.5 per cent, and treatment group 3 (T3) with 2 per  cent supplementation. Standard management and feeding practices were  followed on all treatment groups. The carcass traits such as dressing,  eviscerated and inedible parts percentage were recorded by randomly  selecting two males and two females (four quails) per replicate i.e. six  males and six females (12 quails) from each treatment group and executing  a slaughter study at 35 days of age. The results revealed a significantly  better (P
Keywords: Aloe vera; Japanese quail; carcass traits; dressing percentage; carcass yield